1楼:新野旁观者
√(5+2√6)+√(7-4√3)-√(6-4√2)√(√2+√3)的平方+√(2-√3)的平方-√(2-√2)的平方= √2+√3+2-√3-2+√2
=2√2
2楼:匿名用户
5+2√
6=(1+√5),7-4√3=7-2√12=(√3-√4),6-4√2=6-2√8=(2-√2),代入原式,求得,原式=1+√5-√3+√4+2-√2=3+√5+√4-√3-√2
化简 √(5-2√6)+√(7-4√3)-√(6-4√2) 快点谢谢
3楼:匿名用户
首先√(5-2√6)=√(3+2-2√(2*3))=√((√3)-2*√2*√3+(√2)=√(√3-√2)=√3-√2 (1)
然后√(7-4√3)=√(4+3-2*2*√3)=√(2-2*2*√3+(√3))=√(2-√3)=2-√3 (2)
最后√(6-4√2)=√(4+2-2*2*√2)=√(2-2*2*√2+(√2))=√(2-√2)=2-√2 (3)
所以整个式子化简(1)+(2)-(3)得
0最后结果是0
4楼:匿名用户
原式=√3-√2+2-√3-(2-√2)=0
计√(5+2√6) +√(7-4√3) -√(6-4√2)
5楼:谭银光
5+2√6=(√3+√2)^2
所以√(5+2√6)=√3+√2
√(7-4√3)=2-√3
√(6-4√2)=2-√2
原式=4
化简√(5+2√6 ) +√(7-4√3) +√(6-4√2)
6楼:宇文仙
5+2√
6=2+2√2*√3+3=(√2+√3)7-4√3=4-2*2*√3+3=(2-√3)6-4√2=4-2*2*√2+2=(2-√2)所以√(5+2√6)+√(7-4√3)+√(6-4√2)=√(√2+√3)+√(2-√3)+√(2-√2)=√2+√3+2-√3+2-√2=4
化简 √(5-2√6)+√(7-4√3)-√(6-4√2) 数学
7楼:蓝色de梦幻
^:(根号
bai3 - 根号
du2)^2=5-2根号zhi6;
:(根号dao4 - 根号3)^2=7- 4根号3;
:(根号4 - 根号2)^2=6-4根号2;
各取算术根得:
√(版5-2√6)权]=(根号3 - 根号2)√(7-4√3)]=(根号4 - 根号3)[√(6-4√2)] =(根号4 - 根号2)故原式得:[√(5-2√6)]+[√(7-4√3)]-[√(6-4√2)]
=(根号3 - 根号2)+(根号4 - 根号3)-(根号4 - 根号2)= 0
8楼:葛尚
=(√3-√2)+(√4-√3)-(√4-√2)=0
√5-2√6+√7-4√3-√6-4√2
9楼:小南vs仙子
√5-2√6+√7-4√3-√6-4√2
=√(3-2√6+2)+√(4-4√3+3)-√(4-4√2+2)=√(√3-√2)^2+√(2-√3)^2-√(2-√2)^2=√3-√2+2-√3-2+√2=0